2015
DOI: 10.1002/jcb.25403
|View full text |Cite
|
Sign up to set email alerts
|

Incretinomimetic and Insulinomimetic Effect of (2E)‐N′‐(1′‐Naphthyl)‐3,4,5‐Trimethoxybenzohydrazide for Glycemic Homeostasis

Abstract: To characterize the role and the mechanism of action of (2E)-N'-(1'-naphthyl)-3,4,5-trimethoxybenzohydrazide (BZD) on incretin secretion, glucose uptake in skeletal muscle and α-glucosidase activity on intestine, targets for glucose homeostasis. It was assayed on glucose tolerance test (GTT) to analyze GLP-1 secretion and the activity of DPP-4 enzyme in vitro. In skeletal muscle, mechanism of action on glucose uptake was carried out by in vitro experiments. The activity of intestinal disaccharidases was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…After that slides were processed with AEC Reagent (Zymed Laboratories, San Francisco, CA) and counterstained with hematoxylin (Sigma Co, St. Louis, MO). Ultimately cells were examined and taken the images under bright field .…”
Section: Methodsmentioning
confidence: 99%
“…After that slides were processed with AEC Reagent (Zymed Laboratories, San Francisco, CA) and counterstained with hematoxylin (Sigma Co, St. Louis, MO). Ultimately cells were examined and taken the images under bright field .…”
Section: Methodsmentioning
confidence: 99%
“…GLP‐1 was estimated by means of colorimetric measurements at 450 and 590 nm with an ELISA plate reader (Organon Teknika) by interpolation from a standard curve. Samples were analyzed in duplicate using five rats in each group and results were expressed as serum pM of GLP‐1 [Silva Frederico et al, ].…”
Section: Methodsmentioning
confidence: 99%
“…Then the plate was incubated for 30 min at 37°C. After, the measurement of fluorescence in a multimode reader Infinite M200-TECAN 1 using a black 96-well plate [Silva Frederico et al, 2015], and the results were expresses as relative DPP-4.…”
Section: Dpp-4 Inhibition Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that sulfonylureas activate TRPA1 receptors, potentiating the secretory effect of β cells; however, the mechanism of activation of these channels has not been elucidated (Babes et al, 2013). As such, new compounds based on the fundamental structure of glibenclamide, such as sulfonamides (Hosseinzadeh et al, 2013;Frederico et al, 2016;Frederico et al, 2017) and sulfonyl(thio)urea (Mascarello et al, 2014), have been developed with a view to determine their insulin secretagogue activities and actions on target tissues of glucose homeostasis.…”
Section: Introductionmentioning
confidence: 99%